The Future of Futurism : From the Italian Revolution to Contemporary Art : From Boccioni to Fontana to Damien Hirst - Pietrantonio, Giacinto Di; Rodeschini Galati, Cristina; GAMeC (Galleria d'Arte Moderna e Contemporanea), Bergamo (Bergamo Milano : Electa Editrice Milano GAMeC (Galleria d'Arte Moderna e Contemporanea) Bergamo, 2007)
Accardi, Carla ; Acconci, Vito ; Ackermann, Franz ; Alchimia ; Alviani, Getulio ; Archigram ; Archizoom Association ; Armleder, John ; Baldessari, Roberto ; Balla, Giacomo ; Berlewi, Henryk ; Bertelli, Renato ; Birnbaum, Dara ; Boccioni, Umberto ; Boeri, Stefano ; Breitz, Candice ; Burkovsky, Nicolay ; Cage, John ; Carrà, Carlo ; Catalá i Pic, Pere ; Cattelan, Maurizio ; Chashnik, Ilya ; Chia, Sandro ; Chiari, Giuseppe ; Chiattone, Mario ; Citroen, Paul ; Comerio, Luca ; Cook, Peter ; Cordero, Tina ; Costa, Toni ; Cragg, Tony (Anthony) ; Crali, Tullio ; Creed, Martin ; Debord, Guy ; Delaunay, Sonia ; Depero, Fortunato ; Diulgheroff, Nicolay ; Domela-Nieuwenhuis, César ; Dorazio, Piero ; Duchamp, Marcel ; Fabre, Marcel ; Fabro, Luciano ; Fillia ; Fontana, Lucio ; Fournier, Colin ; Fuksas, Massimiliano ; Gallizio, Pinot ; Garaicoa, Carlos ; Gehry, Frank O. ; Gilbert & George ; Goncharova, Natalia ; Hadid, Zaha M. ; Haring, Keith ; Hirst, Damien ; Höller, Carsten ; Horowitz, Jonathan ; Kcho ; Kingelez, Bodys Isek ; Klutsis, Gustav Gustavovich ; Kruger, Barbara ; Kudriashev, Ivan ; Kupka, Frantisek ; Leger, Fernand ; Levi, Corrado ; Linke, Armin ; Lissitzky, El ; Longo, Robert ; Lye, Len ; Magaril, Evgenia Markovna ; Manzoni, Piero ; Marchi, Virgilio ; Mari, Enzo ; Marinetti, Filippo Tommaso ; Martina, Guido ; Massironi, Manfredo ; Mauri, Fabio ; Mayakovsky, Vladimir ; McCarthy, Paul ; Mendini, Alessandro ; Miyajima, Tatsuo ; Mochetti, Maurizio ; Moholy-Nagy, Laszlo ; Morgunoff, Alexei ; Munari, Bruno ; Nauman, Bruce ; Nouvel, Jean ; Oriani, Pippo ; Paik, Nam June ; Pannaggi, Ivo ; Parc, Julio Le ; Pettena, Gianni ; Piacentino, Gianni ; Pistoletto, Michelangelo ; Popova, Liubov ; Prampolini, Enrico ; Rammellzee ; Rauschenberg, Robert ; Rodchenko, Alexander ; etc.
Artists and works p. 208-239
Publication on the occasion of the exhibition 'The Future of Futurism' at the GAMeC (Galleria d'Arte Moderna e Contemporanea) in Bergamo, 21.09.2007 - 24.02.2008
boek